2022
DOI: 10.1186/s40779-022-00404-0
|View full text |Cite
|
Sign up to set email alerts
|

Propionate and butyrate attenuate macrophage pyroptosis and osteoclastogenesis induced by CoCrMo alloy particles

Abstract: Background Wear particles-induced osteolysis is a major long-term complication after total joint arthroplasty. Up to now, there is no effective treatment for wear particles-induced osteolysis except for the revision surgery, which is a heavy psychological and economic burden to patients. A metabolite of gut microbiota, short chain fatty acids (SCFAs), has been reported to be beneficial for many chronic inflammatory diseases. This study aimed to investigate the therapeutic effect of SCFAs on ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…Butyrate and propionate are known to signal through the G-protein coupled receptor, the free fatty acid receptor 3 (FFA3) while acetate preferentially signals though free fatty acid receptor 2 (FFAR2) 22 . Similar results were observed in macrophages, where propionate and butyrate but not acetate strongly inhibited inflammatory response 23 . Interestingly, butyrate and propionate also possess anti-inflammatory properties in other cell types such as iPSC-derived intestinal epithelia and periodontal tissue 24 , 25 .…”
Section: Discussionsupporting
confidence: 76%
“…Butyrate and propionate are known to signal through the G-protein coupled receptor, the free fatty acid receptor 3 (FFA3) while acetate preferentially signals though free fatty acid receptor 2 (FFAR2) 22 . Similar results were observed in macrophages, where propionate and butyrate but not acetate strongly inhibited inflammatory response 23 . Interestingly, butyrate and propionate also possess anti-inflammatory properties in other cell types such as iPSC-derived intestinal epithelia and periodontal tissue 24 , 25 .…”
Section: Discussionsupporting
confidence: 76%
“…NLRP3‐dependent caspase‐1 cleavage could specifically cleave GSDMD, which controls IL‐1 β release. [ 31 , 32 , 33 ] Correspondingly, GSDMD cleavage and IL‐1 β secretion were also blocked by GGC in a dose‐dependent manner (Figure 6C,D ). The expression levels of caspase‐1 and IL‐1 β were also detected in joint specimens.…”
Section: Resultsmentioning
confidence: 82%
“…It is widely acknowledged that bone homeostasis is maintained and orchestrated by osteoclast-mediated bone resorption and osteoblast-mediated bone formation [ 53 ]. Abundant studies have shown that under the influence of the space microgravity environment, bone homeostasis is unbalanced and osteoclast absorption becomes active, ultimately leading to bone loss [ 54 – 56 ]. Our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%